Bagnold Dunes Campaign Phase 2: Visible/Near‐Infrared Reflectance Spectroscopy of Longitudinal Ripple Sands. Issue 18 (27th September 2018) - Johnson, Jeffrey R.; Bell, James F.; Bender, Steve; Cloutis, Edward; Ehlmann, Bethany; Fraeman, Abigail; Gasnault, Olivier; Maurice, Sylvestre; Pinet, Patrick; Thompson, Lucy; Wellington, Danika; Wiens, Roger C.
Abstract: As part of the Phase 2 Bagnold Dune campaign at Gale Crater, Mars, constraints on the geochemistry, mineralogy, and oxidation state of pristine and disturbed linear sand ripples were made using visible/near‐infrared spectral observations for comparison to Phase 1 spectra of the barchan dunes to the north. Spectra acquired by the ChemCam and Mastcam instruments (400–1, 000 nm) at four Phase 2 locations revealed similar overall spectral trends between the two regions, but most Phase 2 sands were redder in the visible wavelengths. The majority of targets exhibited lower red/infrared ratios, higher ~530‐nm band depths, and higher red/blue ratios than Phase 1 samples, suggesting a greater proportion of redder, fine‐grained, ferric sands in Phase 2 samples. This is consistent with the slightly greater proportion of hematite in Phase 2 samples as determined from CheMin analyses of the Ogunquit sands, which may reflect contamination from the surrounding hematite‐bearing Murray formation bedrock. Plain Language Summary: The Mars Science Laboratory Curiosity rover visited the southern portion of the Bagnold Dunes to look for differences in the types of sand grains that comprised the dunes and ripples. The rover's cameras and spectrometers provided information about the color of the sands, which was used to infer the composition and types of minerals. Overall, the sands in this part of the Bagnold Dunes were a bit redder than those further to the north that were studied previously. We interpreted this to mean that the southern sands contained more oxidized (rusted) iron particles. Because the rocks surrounding these dunes were known to contain a fair amount of red, iron‐rich minerals, it is probable that the sands were mixed with a small amount of broken fragments from these rocks. Key Points: Bagnold Phase 2 sands exhibit higher 535‐nm band depths and red/blue ratios and lower 600‐/700‐nm ratios than Bagnold Phase 1 sands Phase 2 sands contain a greater amount of redder, ferric materials, likely owing to minor hematite contamination from nearby bedrock